Variant of Lemierre's Syndrome Secondary to Trauma - Sani M. Bukari; Renato Roxas; Deepak Kamat (Hindawi Limited, 2010)
Classic Lemierre's syndrome is a septic internal jugular venous (IJV) thrombophlebitis secondary to oropharyngeal anaerobic infection in adolescent and young adult. Though upper respiratory tract infection is the most common antecedent, it has also been described following skin, soft tissues, genitourinary and gastrointestinal infections. Fusobacteria necrophorum is the commonest pathogen isolated from blood and tissue cultures but other bacteria like Eikenella correndens, Bacteroides melaninogenicus and Non Group A Streptococcal species have also been reported. The overall incidence of Lemierre's and Lemierre's like syndromes has declined since the first case report in 1936. There is however, a resurgence of cases in recent years due to more judicious use of antibiotics for treatment of upper respiratory tract infection among medical practitioners. The main stay of treatment of complete Lemierre's syndrome is prolonged antibiotic coverage and surgical drainage of nonresolving abscesses. Currently, there is no consensus opinion on the use of anticoagulation in patient with complete Lemierre's syndrome complicated by septic internal jugular thrombosis and embolism. High index of suspicion is required for early diagnosis of Lemierre's and Lemierre's like syndromes. Early and effective antibiotics therapy may prevent the development full spectrum of the syndrome and its associated complication.